If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.3(2z+5)+2.9=0.4(2z-4)
We move all terms to the left:
0.3(2z+5)+2.9-(0.4(2z-4))=0
We multiply parentheses
0.6z-(0.4(2z-4))+1.5+2.9=0
We calculate terms in parentheses: -(0.4(2z-4)), so:We add all the numbers together, and all the variables
0.4(2z-4)
We multiply parentheses
0.8z-1.6
Back to the equation:
-(0.8z-1.6)
0.6z-(0.8z-1.6)+4.4=0
We get rid of parentheses
0.6z-0.8z+1.6+4.4=0
We add all the numbers together, and all the variables
-0.2z+6=0
We move all terms containing z to the left, all other terms to the right
-0.2z=-6
z=-6/-0.2
z=+30
| 3x+5x+25=3 | | 4(x-2)-5(2x-6)=8(x+1)-3(2+3) | | 13+9x=10.5-1 | | -0.2(x-7.5)=8.9 | | 9x=-3.5 | | 16y=12^2 | | a-(-5-2a)=7(a-1)-2 | | 6x/15=5 | | .32x=2.1x+8.8 | | 6x/15+15=20 | | 2y/7*7/8=13/56 | | 2.7=21.2-x | | y+0.4^-2=6 | | 8x+13=9x+1 | | 8a-8=8a+8 | | 7(10-x=126 | | 25(x-8)^2=81 | | 18.9q^2-7560q-1008000=0 | | 13.65q^2-3276q-814000=0 | | 7d-12d=20 | | 5=17+3r | | x+1/4=-1/7 | | -1=-8–v | | 1.2=3y+15.9 | | 0.3(3z+6)+31.2=0.6(3z-5) | | 1.5=2y+10.9 | | 6/7(x+1)=1/14(x+2) | | -2/5x+14=-54 | | 4m=272 | | 8/4x+x=32 | | 0.5(4z+5)+10.7=0.7(4z-4) | | 3n+2.6=6.2 |